Changes in physical functioning over 6 years in older women: effects of sitting time and physical activity. - Peeters, Geeske; Lips, Paul; Brown, Wendy (European Journal of Ageing, 2014)
The combined effects of physical activity (PA) and sitting time (ST) on physical functioning (PF) may be stronger than for each factor separately. This study examined associations between ST, PA, and PF over 6 years in older women. Data were from 6,611 participants in the Australian Longitudinal Study on Women's Health (mean age 78 ± 1.5 years). Activity pattern at baseline (2002) was categorized as one of 12 combinations of ST (<4, 4-7, or ≥8 h/day) and PA (<40, 40-450, 450-900, or ≥900 MET min/week). PF was measured using the SF-36 (range 0-100) in 2002, 2005, and 2008. General estimating equations for linear regression were used with adjustment for confounders. Baseline PF ranged from 40 to 74 in the least to the most active groups. PF was 6.3 (95 % confidence interval [CI] −7.6 to −5.0) points lower in participants sitting ≥8 h/day than in participants sitting <4 h/day, and 16.9 (CI 15.7-18.0) points higher in participants reporting ≥900 MET min/week than in participants reporting <40 MET min/week PA. Compared with the least active pattern, those in the most active pattern scored 24.5 (CI 22.5-26.4) points higher. The decline over 6 years was greater in the more active categories: 5 and 16 points in the least and most active categories. In conclusion, in women, both high physical activity and low sitting time are important for establishing a certain level of PF prior to age 76-81, but do not protect against decline in PF over time later in life. The combined effect of ST and PA did not differ from their individual effects on PF.